2016
DOI: 10.1016/j.rmcr.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Fatal hemorrhagic pneumonia: Don’t forget Stenotrophomonas maltophilia

Abstract: We present a case of fatal hemorrhagic pneumonia secondary to Stenotrophomonas maltophilia in a patient with acute myeloid leukemia. S. maltophilia is commonly a non-virulent pathogen. However, in the immunocompromised, it is generally associated with bacteremia after central venous catheter placement or pneumonia. Hemorrhagic pneumonia is a rare presentation of this bacteria, with only 31 cases reported in the literature, and has 100% mortality within 72 hours. Rapid recognition and early suspicion should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…In addition, it was recently reported that SM can cause fatal hemorrhagic pneumonia in severely immunocompromised patients who have undergone anticancer chemotherapy or stem cell transplantation (2)(3)(4)(5)(6)(7)(8). Although some cases of SM hemorrhagic pneumonia have been reported, the exact mechanism by which SM causes hemorrhaging as well as the risk factors involved remain unknown (9). However, due to the very high mortality of SM hemorrhagic pneumonia (2), the urgent detection of the characteristics of the disease is required.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was recently reported that SM can cause fatal hemorrhagic pneumonia in severely immunocompromised patients who have undergone anticancer chemotherapy or stem cell transplantation (2)(3)(4)(5)(6)(7)(8). Although some cases of SM hemorrhagic pneumonia have been reported, the exact mechanism by which SM causes hemorrhaging as well as the risk factors involved remain unknown (9). However, due to the very high mortality of SM hemorrhagic pneumonia (2), the urgent detection of the characteristics of the disease is required.…”
Section: Introductionmentioning
confidence: 99%
“…Walaupun demikian, infeksi pada tempat lain seperti aliran darah, selulitis, osteomielitis, saluran kencing, dan infeksi nosokomial telah dilaporkan pada studi sebelumnya. 15,16 Bakteri tersebut memiliki ciri khas yaitu resisten terhadap berbagai antibiotik, dari trimetropim-sulfametoksasol hingga karbapenem oleh karena rendahnya permeabilitas membran sel, disertai adanya produksi enzim beta-laktamase yang didapatkan secara alamiah. 17,18 Hal ini dijumpai pula pada kasus pertama yaitu didapatkan kuman tersebut resisten pada berbagai antibiotik dan memiliki aktivitas intermediate terhadap levofloksasin.…”
Section: Diskusiunclassified
“…The extracellular protease secreted by SM is reported to cause tissue destruction, vascular damage, and subsequent hemorrhage [2][3][4]. Although pulmonary hemorrhage (PH) is an uncommon complication of SM respiratory infection, previous studies have reported mortality as high as 85% within 30 days of infection onset [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%